A new luminescent lanthanide supramolecular network possessing free Lewis base sites for highly selective and sensitive Cu2+ sensing. Issue 6 (10th May 2016) - Chu, Tianshu; Hu, Yunsong; Wu, Jinlun; Zeng, Chenghui; Yang, Yangyi; Ng, Seik Weng
Abstract : Illustration of the probable quenching mechanism and the qualitative/quantitative relationship between Tb luminescent intensity and the analyte concentration. Abstract : A series of new lanthanide complexes, formulated as [Ln2 (DCSAL)3 (H2 O)11 ]·3DCSAL·4H2 O [Ln = Eu (1 ), Gd (2 ) and Tb (3 ); DCSAL = 3, 5-dichlorosalicylate], have been synthesized and characterized by single crystal X-ray analysis. They are dinuclear clusters and form a 3D supramolecular network via π–π stacking and halogen bonding interactions.3 exhibits strong Tb characteristic emission, whose quantum yield is as high as 38%. Due to binding with Cu 2+ ions via its Lewis acid–base interactions, 3 displayed a high selectivity and sensitivity for Cu 2+ detection based on Tb 3+ emission quenching. The possible quenching mechanism was further proved to be a static quenching mechanism by Stern–Volmer plots and UV-vis spectrum. More importantly, the binding constant between3 and Cu 2+ is also calculated by the Benesi–Hildebrand method, which is helpful for quantitative analysis.